The Difficulties Faced and The Strategies Used by English Department Students in Learning English as a Foreign Language - Muammalah, Muammalah; Misnadin, Misnadin (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2023)
The study aims to identify the difficulties faced and the strategies used by English Department students at Universitas Trunojoyo Madura in learning English. The study used a mixed-method approach, which is a combination of quantitative and qualitative approaches. The source of data was one class in the second semester that consisted of thirty-seven students. The data were the difficulties faced by the students in learning English and the strategies they used to deal with them. The research instrument used was questionnaires containing both close-ended and open-ended questions. The data that was obtained from closed-ended questions were analysed quantitatively while those that were derived from open-ended questions were analysed qualitatively. The results showed that the difficulties faced by English Department students in learning English include pronunciation, grammar, and vocabulary and they exercised different strategies to solve them. Specifically, the strategies to solve the difficulty in learning pronunciation were listening to English songs, singing English songs, watching English movies or films, imitating using Google Translate, and practising the pronunciation by themselves. The strategies to tackle the difficulty in learning grammar were watching YouTube, reading English books, learning from the internet, learning through Instagram, and learning by themselves. Furthermore, there were several ways that they used to deal with the difficulty in learning vocabulary, for example, they used English dictionaries, watched English movies, read English books, used English songs, and memorized new vocabulary.